Political efficacy and political trust among descendants: The significance of perceived public hostility towards Muslims and refugees - Vestergaard Ahrensberg, Nanna; Hansen, Kir; Kriegbaum Jensen, Kristian (Politica, 2021)
How do ethnic minorities integrate politically when they experience a hostile political climate towards non-western immigration? We study this important yet underexplored question through a unique Danish survey from 2018 among 20-30-year-old descendants of immigrants and a control group of Danish origin. This study goes further than earlier studies and analyzes the correlation between young adults’ own perception of public hostility against Muslims and refugees and their political efficacy and political trust. The analysis shows a notably stronger correlation among Muslim descendants, and especially among the most religious of them, but only related to their external political efficacy and political trust. Internal political efficacy is rather unaffected, which indicates an unexploited potential for political mobilization.